Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3109/02713683.2013.845227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Orthostasis and Daytime on Retinal Thickness in Uveitis-Associated Cystoid Macular Edema

Abstract: Intraretinal-fluid in uvCME may show a high mobility: CRT decreases within seconds after a patient changes position, indicating that position effects retinal-thickness. Main diurnal-decrease in CRT occurs before noon, which is likely due to a position-change in the morning. Patient-population (walk-in patients versus hospitalized, lying patients) and previous waiting-position should be considered when interpreting retinal-thickness in clinical-practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies have identified significant diurnal variation of DME on OCT, with the zenith of edema occurring in the morning and tapering to a nadir as the day progresses [ 5 9 ]. Similar diurnal variation of macular edema is also seen on OCT in patients with branch and central retinal vein occlusions (RVO) and in patients with uveitis [ 10 , 11 ]. However, to our knowledge, no studies have investigated potential diurnal variation in eAMD.…”
Section: Introductionmentioning
confidence: 80%
“…Several studies have identified significant diurnal variation of DME on OCT, with the zenith of edema occurring in the morning and tapering to a nadir as the day progresses [ 5 9 ]. Similar diurnal variation of macular edema is also seen on OCT in patients with branch and central retinal vein occlusions (RVO) and in patients with uveitis [ 10 , 11 ]. However, to our knowledge, no studies have investigated potential diurnal variation in eAMD.…”
Section: Introductionmentioning
confidence: 80%